Framing of Flood in Mainstream Newspapers and Readers’ Response to Flood Reporting in China and Malaysia - NING, LI (UNIVERSITI MALAYSIA SARAWAK, 2026)
Past studies on flood news have focused on how the media frame disaster events and how readers respond to the flood news. Few studies have examined how readers react to framing of flood news in terms of their affect, behavior, and cognition. To date, no studies have investigated framing together with qualitative interviews to explore readers’perceptions of flood-related media frames. Therefore, little is known about readers’response to flood news framing in newspapers and how their affect, behavior and cognition may be influenced by media systems and disaster communication environments in different countries. The study examined the framing of flood news in mainstream newspapers and reader’ response to flood reporting in China and Malaysia. The objectives of the study were to: (1) analyze inter-relationships between episodic and thematic framing of floods vis-a-vis frame dimensions in selected national and regional newspapers in China and Malaysia; (2) determine the dominant valence of news articles on flood events in selected national and regional newspapers in China and Malaysia; (3) examine readers’responses to reporting of flood events in China and Malaysia; and (4) explore how framing of flood news influences readers’ responses in terms of attitudes, behavior and cognition. The newspaper articles analyzed were 411 articles (147,187 words) published from 1 January to 31 December 2023 in two national newspapers (People’s Daily in China, The Star in Malaysia) and two regional newspapers (Zhengzhou Daily in China, The Borneo Post in Malaysia). The results showed the high frequency of episodic frames (96.5%) and lack of thematic articles (3.5%). The two newspapers in China have predominant positive valence,particularly People’s Daily (79.6%) which is more than Zhengzhou Daily (30.8%) and the Malaysian newspapers (The Star, 53%; The Borneo Post, 39.5%). In contrast, the two newspapers in Malaysia were more neutral (The Star, 9.1%; The Borneo Post, 18.4%) than the two newspapers in China (People’s Daily, 2.6%; Zhengzhou Daily, 23.1%), and this may help readers to develop critical perspectives on flood management by authorities. The dominant frame dimension in flood news articles was responsibility (People’s Daily, 81.5%; Zhengzhou Daily, 76.9%; The Star, 64%; The Borneo Post, 79%). The focus of the newspapers in China was on government efforts but the focus of the newspapers in Malaysia was institutional response. The human interest frame was minimally used due to the fact-focused reporting (People’s Daily, 1.3%; Zhengzhou Daily, 15.4%; The Star,10.3%; The Borneo Post, 3.9%). The conflict frame was absent in Chinese newspapers and minimal in Malaysian newspapers (The Star, 1.2%; The Borneo Post, 1.3%). The morality frame was not used in any of the flood news articles in the four newspapers. To elicit reader responses to flood reporting, semi-structured interviews were conducted with 40 participants (20 China, 20 Malaysia). Thematic analysis based on Rosenberg et al.’s (1960) Affect-Behavior-Cognition model showed differences for China and Malaysia, and between flood victims (13 in China and 15 in Malaysia) and those who did not experience floods (7 in China and 5 in Malaysia). The responsibility frame was common in both countries. Chinese readers appreciated incident-based reporting but Malaysian readers were frustrated by the dominance of episodic frames. Chinese readers generally trusted the authorities to manage the flood crisis, whereas Malaysian readers demanded clearer accountability from the authorities. Chinese readers obtained emotional reassurance from the positive valence of flood news articles in the Chinese national newspaper but Malaysian readers expressed a preference for greater use of the human interest frames to foster empathy and public support because they have been seeking updates and emotional information shared through social media. The findings suggests that in China where there is strict media control, the newspapers can shape the affect, behavior and cognition of the readers but readers in Malaysia have more critical thinking towards the flood news reporting because of less strict media control. Keywords: Flood, newspaper, framing, episodic frame, thematic frame, valence, frame dimensions, readers’ response, China, Malaysia